Salivary cortisol concentrations in hematogy/oncology nurses on working days and days off - Monique Pereira Portella Guerreiro; Graziele de Lima Dalmolin; Rafaela Andolhe; Eniva Miladi Fernandes Stumm; Matias Nunes Frizzo; Taís Carpes Lanes
ABSTRACT Objective: to assess salivary cortisol concentrations in hematology/oncology nurses on working days and days off. Methods: a cross-sectional study carried out with 28 nurses from a university hospital. A sociodemographic, employment and health profile questionnaire was applied. For saliva collection, Salivette® tubes were used. Descriptive and analytical analysis was used. Results: there was no significant difference in cortisol concentrations between working days and days off (p>0.05). The high cortisol concentration was associated with not having children (0.621±0.340; p=0.046), not using medication (0.623±0.133; p=0.017) and birth control pills (0.556 ± 0.228; p=0.047) and intention to leave work (0.951±0.154; p=0.001). A positive correlation was identified between cortisol and absence from work due to health issues (0.72; p=0.05) and weight gain (0.935; p=0.02). Conclusion: in general, cortisol concentration is within the reference parameters, with no significant difference in its secretion on working days and days off.